Sanitary Protection of the Territories within the Frames of Sanitary-Epidemiological Welfare Provision - A. E. Shiyanova; V. P. Toporkov; M. N. Lyapin; I. G. Karnaukhov (Проблемы особо опасных инфекций, 2015)
Demonstrated is the structural and functional interrelation between sanitary protection of the territories, epidemiological monitoring, and the state sanitary-epidemiological surveillance. Sanitary protection of the territories (SPT) of the Russian Federation is a separate focus area authorizing sanitary prophylactic (anti-epidemic) activities, with a self-sustained sub-goal. It combines individual roles appertained to epidemiological monitoring and to federal sanitary-epidemiological surveillance, only in reference to a particular item - emergency situation in the sphere of sanitary-epidemiological welfare of the population. Specificity of the SPT is a balance between functionality and capacity of the monitoring, surveillance and control. Legislative and regulatory legal acts, which concern sanitary protection of the territory, provide the means for defining its basic organizational principles: country-wide activities, self-sufficiency and self-support of the Rospotrebnadzor, three-level hierarchical system, and information exchange.